The risks of using allogeneic cell lines for vaccine production: the example of Bovine Neonatal Pancytopenia - Lindert Benedictus; Charlotte R. Bell (Taylor & Francis Group, 2017)
Introduction: Bovine neonatal pancytopenia (BNP) is a hemorrhagic disease that emerged in calves across Europe in 2007. Its occurrence is attributed to immunization of the calf's mother with a vaccine produced using an allogeneic cell line. Vaccine-induced alloantibodies specific for major-histocompatibility class I antigens are transferred from the mother to the calf via colostrum, leading to profound depletion of peripheral blood and bone marrow cells that is often fatal. Areas covered: Pubmed and Web of Science were used to search for literature relevant to BNP and the use of allogeneic vaccine cell lines. Following a review of the pathology and pathogenesis of this novel condition, we discuss potential risks associated with the use of allogeneic vaccine cell lines. Expert commentary: Although BNP is associated with a specific vaccine, it highlights safety concerns common to all vaccines produced using allogeneic cell lines. Measures to prevent similar vaccine-induced alloimmune-mediated adverse events in the future are discussed.